Crosstalk : Canadian and Global Imaginaries in Dialogue - Dvorak, Marta; Brydon, Diana (Book collections on Project MUSE., 2012)
"What are the fictions that shape Canadian engagements with the global? What frictions emerge from these encounters? In negotiating aesthetic and political approaches to Canadian cultural production within contexts of global circulation, this collection argues for the value of attending to narratorial, lyric, and theatrical conventions in dialogue with questions of epistemological and social justice. Using the twinned framing devices of crosstalk and cross-sighting, the contributing authors attend to how the interplay of the verbal and the visual maps public spheres of creative engagement today. Individual chapters present a range of methodological approaches to understanding national culture and creative labour in global contexts. Through their collective enactment of methodological crosstalk, they demonstrate the productivity of scholarly debate across differences of outlook, culture, and training. In highlighting convergences and disagreements, the book sharpens our understanding of how literary and critical conventions and theories operate within and across cultures."--Publisher's website